Lithological Discrimination Based on Radiometric Data: Case Study of Rabau Sector, West Kalimantan and Salumati Sector, West Sulawesi - Maulana, Muhammad Wira; Ciputra, Roni Cahya; Iskandarsyah, Iskandarsyah; Adimedha, Tyto Baskara; Sukadana, I Gde; Indrastomo, Frederikus Dian; Syaeful, Heri; Pratiwi, Fadiah; Rachael, Yoshi; Mardania, Faneza Nur; Kamajati, Dhatu; Rahmawati, Putri; Garwan, Mirna Berliana (BRIN Publishing, 2025)
This study evaluates the applicability of radiometric methods for lithological discrimination in tropical environments, with a focus on two uranium exploration sites in Indonesia: the Rabau Sector in West Kalimantan and the Salumati Sector in West Sulawesi. These locations were selected to represent various lithologies within the uranium exploration program. The aim is to determine whether gamma-ray spectrometry, commonly effective in arid environments, can also delineate lithological boundaries and alteration zones under conditions of intense weathering and dense vegetation cover of tropical area. Ground-based radiometric data were collected using the RS-125 gamma spectrometer to record the concentration of potassium (K), equivalent uranium (eU), and equivalent thorium (eTh). Data processing involved anisotropy analysis, geostatistical interpolation using ordinary kriging, ternary RGB composite mapping, and delineation of radiometric domains. The resulting radiometric maps were then qualitatively compared with existing geological maps for validation. The results show that radiometric signatures, particularly eTh and eU, can effectively distinguish rock units with differing genesis or degrees of alteration, despite tropical conditions. In Rabau, where lithologies share a common protolith, elevated eU concentrations correspond to hornfels, while metatuff and metasiltstone remain indistinguishable, indicating the influence of thermal metamorphism on radiometric responses. In Salumati, eTh and eU zoning within phonolite suggest compositional variability or differential alteration, and elevated eU in altered tuff reflects uranium remobilization in smectite-rich zones. These findings demonstrate that, despite the challenges posed by tropical climates, radiometric mapping remains a viable tool for lithological discrimination and early-stage uranium exploration in Indonesia. This work extends the application of radiometric techniques beyond arid environments and underscores the need to integrate radiometric interpretation with genetic, provenance, and alteration context in tropical geological mapping.